Real action based on search solve create and share (SSCS) model to improve sustainability awareness of junior high school students - Evi Suryawati; Y. Yennita; Siti Rahmi Afwa; Putri Rahma Dianti; S. Syafrinal (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Water pollution from manufacturing waste and air pollution from forest and land fires are major environmental issues in the Siak district. This research aimed at gathering empirical data by implementing a real-action project based on SSCS learning to enhance sustainability awareness of Junior High School. This quasi-experiment was carried out in two groups of students in 7th grade of SMPN 1 Koto Gasib, Siak, Riau Province. The experimental class used the SSCS learning model with the ESD approach and the control class applied the scientific learning model. Indicators of sustainability awareness comprise: 1) Sustainability Practice Awareness; 2) Behavioral and Attitude Awareness; and 3) Emotional Awareness. Real-action project that is implemented by the teacher in this research is conducted to promote sustainability awareness in the form of a water purification model, planting pollution-absorbing plants, and creating Eco-brick flower pots. Data analysis uses inferential statistics, namely the T-test using SPSS-26 software. The analysis results of sustainability awareness indicate that students in the experimental class get a higher average of 76%, with the high category. Meanwhile, students in the control class get an average of 65% in the medium category. The T-test analysis of sustainability awareness gets a significance value of 0,002.  0,05, which indicates that there is a significant difference between experimental and control classes. The implementation of SSCS learning model using ESD approach can enhance the students’ sustainability awareness through environmental problem-solving activities, as well as building knowledge, behavior, and attitudes of love for the environment.